Membangun Kepedulian Lingkungan melalui Literasi Ekologis pada Mahasiswa Pendidikan Geografi Universitas Siliwangi - Nur'aini, Fitri; Heryana, Pudja Septia; Rahmawati, Chindi; As’ari, Ruli (Prosiding Seminar Nasional Pendidikan, Ilmu-Ilmu Sosial, dan Hukum (SENPISHUM), 2026)
Environmental concern is a fundamental aspect in maintaining ecosystem sustainability amid increasing global challenges such as climate change, pollution, and natural resource degradation. This study aims to analyze the level of environmental concern among Geography Education students at Universitas Siliwangi and to examine the role of ecological literacy in shaping students’ attitudes, behaviors, and social participation toward environmental preservation. A descriptive quantitative method was employed, with data collected through a Likert-scale questionnaire involving 40 respondents from a total population of 123 students. The analysis identified categories of environmental concern based on three indicators: environmentally concerned attitudes, actual behavior, and social participation. The results indicate that students’ environmental concern is generally high, with scores of 100% for attitudes, 85% for actual behavior, and 80% for social participation. The findings demonstrate that ecological literacy plays a crucial role in fostering students’ awareness and ecological responsibility. Understanding ecological concepts and the interconnection between human activities and the environment encourages pro-environmental behavior. Students’ social participation still requires improvement through the strengthening of ecological literacy-based activities and the support of green campus policies. Ecological literacy serves as a strategic foundation for cultivating sustainable environmental concern in higher education.